PENGARUH DIGITALISASI PENDIDIKAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN MAHASISWA - Wedi Samsudi; Arifatus Solihah; Eva Latipah; Zainal Arifin Ahmad (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
Digitalization of education is a transformation of the learning system through the use of digital technology, which aims to increase the efficiency and effectiveness of the teaching and learning process. This research aims to analyze the effect of digitalization of education on the quality of student learning. The research uses a descriptive quantitative approach. The research method used is a simple linear regression design with data obtained through surveys involving students from various study programs. The research results show that digitalization has a positive impact on increasing accessibility, interactivity and learning efficiency. This shows that the increasing digitalization of education will also increase the quality of student learning. These findings provide important implications for university education in improving technology and creating more flexible, interactive, and efficient learning experiences.